Policy Gaps in Mental Health within Conflict-Affected Middle Eastern Countries : A Regional Synthesis - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
This study conducts an in-depth examination of the structural gaps in mental health policies within conflict-affected countries in the Middle East region, employing a systematic meta-synthesis approach to analyze 87 primary studies published between 2015 and 2024. Findings reveal that only 23.4% of these countries possess mental health policies that can be classified as comprehensive. In comparison, the average budget allocation for this sector accounts for merely 2.1% of total national health expenditures. In terms of affected populations, the prevalence of mental disorders is alarmingly high, recorded at 41.3% among refugees and 37.8% among residents living amidst protracted conflict. Through logistic regression analysis, a highly significant correlational relationship was identified between conflict intensity and the severity of mental disorders (r = 0.78; p < 0.001), underscoring the systemic link between structural violence and collective psychosocial vulnerability. Furthermore, meta-regression successfully identified the five most dominant policy gaps: deficits in service infrastructure (76.5%), shortages of the professional workforce (68.2%), dysfunctions in referral systems (64.7%), limitations in funding (59.3%), and lack of intersectoral service integration (52.8%). This research not only extends the conceptual framework and empirical findings previously advanced by Sihombing et al. (2025) and Akhtar et al. (2021) concerning the mental health impacts of conflict but also innovatively articulates region-specific patterns and identifies contextual moderator variables that influence policy implementation effectiveness. Thus, this study's methodological and conceptual novelty lies in formulating an evaluative framework grounded in empirical evidence, which integratively combines socio-political indicators with clinical mental health parameters, offering a comprehensive approach to assess and reform public policy in conflict-affected areas of the Middle East.